Nonlinear transistor model parameter extraction techniques - Rudolph, Matthias, 1969-; Fager, Christian; Root, David E. (Cambridge RF and microwave engineering series., 2012)
Achieve accurate and reliable parameter extraction using a broad range of techniques and models provided.